KONSEP PENDIDIKAN KARAKTER DALAM PERSPEKTIF KITAB TA’LIMUL MUTA’ALLIM DI PONDOK PESANTREN MODERN AL-IHYA CIGUGUR KUNINGAN - Banu Aji, Restu; Muslim, Hari Bukhori (JURNAL KAJIAN ISLAM MODERN, 2024)
The character approach education sufficiently influences the motivation and learning outcomes of students so that they can provide maximum learning stimulants. The monotony of the learning approach is one of the obstacles in learning activities so that students are less enthusiastic in learning and make learning rigid. This study aims to determine the application of the concept of character education in the perspective of the book of Ta'limul Muta'allim at the Al-Ihya Modern Islamic Boarding School, Cigugur Kuningan. This study uses a qualitative approach and descriptive type. Methods of data collection using the method of observation, interviews and documentation. Data analysis techniques using data reduction, data presentation, and drawing conclusions. While checking the validity of the data using triangulation. The results of his research are: 1) The meaning of education in a simple way can be interpreted as a human effort to develop his personality in accordance with the values in society and culture; 2) The concept of character education for students through Tali'mul Muta'allim learning at the Modern Islamic Boarding School Al-Ihya Cigugur Kuningan is formed by directing students to always behave well, both manners, courtesy towards teachers, and how to respect friends; and 3) The method used in the application of studying for students through Ta'limul Muta'allim learning at the Al-Ihya Cigugur Kuningan Islamic Boarding School is that the teacher always gives directions on how to study well. The teacher teaches how important it is to study for a student. Always directing students that studying is very important for them because to reach their goals they have to use knowledge.